2021
DOI: 10.3390/en14092655
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics, Kinetics, SO2 and NO Release of Low-Grade Biomass Materials and Briquettes

Abstract: The influence of the briquetting process on SO2 and NO release characteristics, combustion properties and kinetic characteristics during biomass combustion was investigated. Two biomass (Wheat straw and Tree bulk) and two obtained briquettes were analysed. The briquetting process helps to prevent the release of SO2 and NO. The experimental results show that once the biomass is made into a briquette, when the reaction temperature is 900 ∘C, the sulphur release ratio for TB was reduced from 34.7% to 4.3% and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, in type B systems, with an increase in the combustion intensity, combustion temperature and CO 2 emissions, the NO emission is determined by conditions in the combustion chamber other than the nitrogen content in the fuel. Additionally, the occurrence of increased NO emissions corresponds to SO x emissions [96]. In terms of SO x emissions, it should be clearly noted that the combustion of biofuels is associated with a significant reduction compared to coal fuels [47,[97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in type B systems, with an increase in the combustion intensity, combustion temperature and CO 2 emissions, the NO emission is determined by conditions in the combustion chamber other than the nitrogen content in the fuel. Additionally, the occurrence of increased NO emissions corresponds to SO x emissions [96]. In terms of SO x emissions, it should be clearly noted that the combustion of biofuels is associated with a significant reduction compared to coal fuels [47,[97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…In previous preliminary studies [105], periodic, batch burning of wheat straw and hay briquettes on a grate indicated significant SO 2 emissions associated with changes in the temperature in the combustion chamber. Qi et al [96] indicate that the process of SO 2 formation from biomass during its combustion is not obvious and is related to many factors, including the following: sulfur content in biomass, combustion temperature and reactive elements that may react with sulfur. Krzywanski et al [106] indicate that the inhibition of CO oxidation occurs in the presence of high SO 2 concentrations, and the increase in the conversion of carbon to CO in the presence of SO 2 also reduces NO emissions.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results [21] show that once the biomass is made into a briquette, when the reaction temperature is 900 ∘ C, the sulphur release ratio for TB was reduced from 34.7% to 4.3% and for WS was reduced from 12.4% to 1.6%. When the reaction temperature increases to 1000 ∘ C, the sulphur release ratio for TB was reduced from 73.4% to 30.4%, for WS it was reduced from 58.4% to 10.2%.…”
Section: Cluster 2 Highlighting Thermal Biomass Processingmentioning
confidence: 97%
“…The transformation of biomass resources could increase energy supply and promote the energy mix. One way to harness biomass resources is by using densification, which is the application of pressure to form solid fuels that have advantages for domestic and industrial application [3][4][5].…”
Section: Introductionmentioning
confidence: 99%